“Aging in Place” – Aging at home and in the community (PerCursos, 2023)
Despite most Portuguese people tend to get older in their homes, measures to promote aging in place continue to have poor public visibility when compared to the attention given to institutional solutions. As a necessary approach to promoting healthy aging, valuing aging in place strategies means responding to the needs of older people based on the contexts in which they live. In practice, this means not removing people from where they live to provide them with what they need but creating conditions there so that their needs are met as they age. It is precisely to verify «how this can be done» the main purpose of this paper, first through a discussion of the concept of “aging in place” and then by the analysis of concrete dimensions of operationalization of this concept, both in Portugal and in other countries.
Keywords: aging in place; community; Portugal; aging